Timeo de Tauromenio. Orígenes de Sicilia. Historiografía griega. - Sánchez Jiménez, Francisco (Gerión. Revista de Historia Antigua, 2013)
The theory, held by Timaeus, that claims the autochtony of the Sicani must be considered, in general terms, as an expression both of Sicilian lore and the origins of Sicily. The Tauromenium historian, who worked in order to organically accumulate the ancient traditions of the island, characterised the Sicani as a people whose simple and authentic mode of life was free from the τρυφή sin.
Keywords: Timaeus of Tauromenium; Origins of Sicily; Greek Historiography.